Citizenship education in (not only) Czech Television - Chrenčík, Roman (Civilia, 2023)
This study deals with the relationship between the Czech media, led by Czech Television, and citizenship education. The conducted research is of a qualitative nature, data collection took place in the form of semi-structured interviews with relevant stakeholders for the fields of education and media. The reality of questioning often turned the topic to the relationship between the media and education in general, as well as to the issue of social responsibility of the media. The research points to the absence of clearly formulated priorities for both key areas, namely civic education and the media. In addition to the specific educational plan, the civic education also lacks personalities who would become the driving force behind this topic. For the media, especially public service ones, there is the demand for the redefinition of the public service and the establishment of clear requirements for Czech Television incl. those regarding the topic of citizenship education.
Keywords: Citizenship education; Czech Television; Public responsibility; Media; Public service